2008
DOI: 10.1002/pola.22962
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic LC copolymers containing azobenzene and crown‐ether groups

Abstract: An approach for the creation of a novel family of multifunctional crown‐ether‐containing comb‐shaped copolyacrylates consisting of chromophoric (azobenzene), ionophoric (crown‐ether), and mesogenic groups in the same macromolecule was developed. Phase behavior of the copolymers was studied, and correlation between their molecular structure and thermal properties was established. The increase of crown‐ether‐containing groups' concentration up to 26 mol % leads to disruption of nematic order and formation of amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…This difference can be explained by the steric hindrance, which suppresses the isomerisation processes and the transition from the rod-like E-isomer to the non-linear Z-isomer of the azobenzene molecules in solid films of compound 2d. Similar effects are well known in the literature for amorphous and LC azobenzene-containing polymers [110][111][112].…”
Section: Techniquessupporting
confidence: 59%
“…This difference can be explained by the steric hindrance, which suppresses the isomerisation processes and the transition from the rod-like E-isomer to the non-linear Z-isomer of the azobenzene molecules in solid films of compound 2d. Similar effects are well known in the literature for amorphous and LC azobenzene-containing polymers [110][111][112].…”
Section: Techniquessupporting
confidence: 59%
“…Regarding the small molecular systems containing two different fully covalent‐bonded components, unusual molecular arrangements and mesomorphic behaviors were developed by blending rod‐like liquid crystals with bent‐core LC dopants 25, 26. Meanwhile, the blended polymeric systems (mainly side‐chain polymers) were expanded by doping,27 copolymerization,28–33 and H‐bonded complexation34 with chiral/achiral LC components to induce the particular mesomorphic and electro‐optical properties. In recent years, some related literatures about H‐bonded polymeric materials and applications of block copolymers have been developed by Hawker's group 35, 36.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that UV‐irradiation of these compound's films leads to an increase of ionic conductivity, but irradiation with the visible light has restored the initial level of conductivity. Recently, we have elaborated and described synthetic approaches for the synthesis of wide range of photochromic crown ether‐containing LC homopolymers and copolymers based on azobenzenes 15, 16. It was shown that complexation of these compounds with metal ions results in a decrease of clearing temperature, and in some cases, formation of complexes leads to a transition into the amorphous state.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we have continued our work launched before 15,16 and have performed synthesis of a series of novel photochromic crown ether-containing polymers with different macromolecular structures. One of the main goals of this work is an investigation of a relation between molecular architecture of the synthesized polymers and photo-optical properties and phase behavior of these polymer materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation